The Strengthening of Religious Moderation Values through Fiqh Learning at MAN 1 Surakarta - Istiqomah Istiqomah; Fauzi Muharom (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Religious moderation has become an important issue in Islamic education, particularly in strengthening students’ attitudes of tolerance, inclusiveness, and social harmony within multicultural societies. This study aims to analyze the reinforcement of religious moderation values through Fiqh learning at MAN 1 Surakarta. The research focuses on three main aspects, namely the planning, implementation, and evaluation of Fiqh learning in strengthening students’ moderate religious attitudes. This study employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation. The research subjects consisted of Fiqh teachers and twelfth-grade students of the regular program at MAN 1 Surakarta, while the vice principal for curriculum affairs served as the key informant. Data validity was examined using source triangulation and method triangulation. Data analysis was conducted through data reduction, data display, and conclusion drawing based on the Miles and Huberman model. The findings reveal that the reinforcement of religious moderation values in Fiqh learning was systematically integrated into learning objectives, teaching materials, learning methods, and classroom interactions. Teachers introduced differences among Islamic schools of thought as a means to cultivate tolerance and respect for diversity. The learning process was carried out dialogically and reflectively through discussions, contextual explanations, and the habituation of respectful attitudes. In addition, the evaluation process emphasized not only cognitive achievement but also students’ social attitudes and daily behavior. The study concludes that Fiqh learning at MAN 1 Surakarta plays a significant role in shaping moderate, tolerant, and inclusive students through continuous integration of religious moderation values in both classroom learning and the broader madrasa environment.